Gradient dynamical systems for principal singular subspace analysis - Hasan, M.A.; Hasan, J.A.K. (2008 American Control Conference, 2008)
Principal singular component analysis has recently been proposed and analyzed by the author. It is a generalization of the principal singular subspace analysis which has been investigated in the literature. In this paper an unconstrained weighted cost function is utilized to develop dynamical systems that converge to the actual principal singular vectors of a given matrix. Stability analysis that reveals the domains of attraction of these systems is also given.